In Vivo Imaging of Cardiac Attachment of TcI and TcII Variants of Trypanosoma cruzi in a Zebrafish Model - Victoria E. Rodriguez-Castellanos; Cristhian David Perdomo-Gómez; Juan Carlos Santos-Barbosa; Manu Forero-Shelton; Verónica Akle; John M. González (Pathogens)
Trypanosoma cruzi, the etiological agent of Chagas disease, is a parasite known for its diverse genotypic variants, or Discrete Typing Units (DTUs), which have been associated with varying degrees of tissue involvement. However, aspects such as parasite attachment remain unclear. It has been suggested that the TcI genotype is associated with cardiac infection, the most common involved site in chronic human infection, while TcII is associated with digestive tract involvement. Traditional models for T. cruzi infection provide limited in vivo observation, making it challenging to observe the dynamics of parasite-host interactions. This study evaluates the cardiac attachment of trypomastigotes from TcI and TcII DTUs in zebrafish larvae. Labeled trypomastigotes were injected in the duct of Cuvier of zebrafish larvae and tracked by stereomicroscopy and light-sheet fluorescence microscopy (LSFM). Remarkably, it was possible to observe TcI parasites adhered to the atrium, atrioventricular valve, and circulatory system, while TcII trypomastigotes demonstrated adhesion to the atrium, atrioventricular valve, and yolk sac extension. When TcI and TcII were simultaneously injected, they both attached to the heart; however, more of the TcII trypomastigotes were observed attached to this organ. Although TcII DTU has previously been associated with digestive tissue infection, both parasite variants showed cardiac tissue attachment in this in vivo model.